Governmental regulation induced pesticide retailers to provide more accurate advice on pesticide use to farmers in China - Li, Zhongju; Hu, Ruifa; Zhang, Chao; Xiong, Yankun; Chen, Kevin Z. (Wiley, 2022)
In China, pesticide retailers have often been accused of providing inaccurate advice on pesticide use to farmers in a chaotic pesticide market. However, it is unclear whether governmental regulation of sales and advice on pesticide use by pesticide retailers induces them to provide accurate advice.Using survey data of 242 pesticide retailers in 2016, this study analyzes how pesticide retailers in China provide advice on pesticide use to farmers and examines whether governmental regulation induces pesticide retailers to provide accurate advice. The surveyed retailers were found to advise farmers to use the correct active ingredients in only 75.6% of observations. Retailers recommended pesticide application rates higher than the scientifically recommended levels among 57.2% of observations. The bivariate probit model estimation results show that highly intensive governmental regulation increases the probability of correct advice on pesticide use of pesticide retailers in the county and township seats by 13% and 19%, respectively. Moreover, highly intensive regulation can also increase the probability of pesticide non‐overuse advice by the retailers from the retailers in the villages by 38%.Highly intensive governmental regulation can induce pesticide retailers to provide more accurate advice on pesticide use to farmers, but the effects differ across the locations of pesticide retailers. © 2021 Society of Chemical Industry.